2006
DOI: 10.1016/j.jmacro.2005.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Monetary policy and long-term US interest rates

Abstract: This paper assesses the effect of federal funds rate innovations on longer-term US nominal interest rates across different periods. The evidence suggests that these responses change with changes in the monetary policy regime. Time periods considered are pre-and post-1979 and different Federal Reserve Chairman's tenure. The response of longer-term interest rates to federal funds rate innovations are shown to be smaller and less persistent in the post-1979 period when the Federal Reserve placed more emphasis on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 23 publications
1
16
0
Order By: Relevance
“…It takes into account the proportion of the adjustment, which takes place in the first period and the total adjustment in the long run. Robustness of these results obtained from the ECM estimates are formally checked by estimating bivariate VAR models and comparing impulse responses as suggested by Diebold and Sharpe (1990);De Bondt (2005) and Berument and Froyen (2006).…”
Section: /mentioning
confidence: 99%
“…It takes into account the proportion of the adjustment, which takes place in the first period and the total adjustment in the long run. Robustness of these results obtained from the ECM estimates are formally checked by estimating bivariate VAR models and comparing impulse responses as suggested by Diebold and Sharpe (1990);De Bondt (2005) and Berument and Froyen (2006).…”
Section: /mentioning
confidence: 99%
“…Looking at the longest time period , while the effect of a change in the federal funds rate on the 1-year interest rate is smaller, the effect on the long-term rate, as measured by the 10-year rate, is close to that of Edelberg and Marshall and Evans and Marshall. The Berument and Froyen (2006) VAR study for the period of the Greenspan chairmanship (Table 1, line 5) shows little significant effect of monetary policy actions on the 10-year interest rate.…”
Section: Some Previous Var Resultsmentioning
confidence: 99%
“…Based on a VAR analysis for the sample period 1964-1995 and employing three methods for identification of the system, they conclude that long-term rates are "virtually unaffected" by monetary policy actions. Berument and Froyen (2006) estimate VARs with weekly data from 1975 to 2002 and consider various sub-periods. Estimated effects of changes in the federal funds rate on long-term interest rates from their study are shown in lines 5-7 of Table 1.…”
Section: Some Previous Var Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…6 Another explanation could be put forward is that the economic performance is affected by long term interest rates but not short term interest rate (Bernanke and Reinhart, 2004). If the relationship between long and short term interest rates are not stable (evidence on this issue one may look at Berument and Froyen, 2006), then, the innovations on short term interest rate (interbank interest rate here) may not 6 See Mishkin (1996) for an overview of the transmission mechanisms of monetary policy.…”
Section: Discussion and Policy Implicationsmentioning
confidence: 99%